2023
DOI: 10.1097/cm9.0000000000002562
|View full text |Cite
|
Sign up to set email alerts
|

Flare and change in disease activity among patients with stable rheumatoid arthritis following coronavirus disease 2019 vaccination: a prospective Chinese cohort study

Abstract: Background: Vaccination has been shown effective in controlling the global coronavirus disease 2019 (COVID-19) pandemic and reducing severe cases. This study was to assess the flare and change in disease activity after COVID-19 vaccination in patients with stable rheumatoid arthritis (RA). Methods: A prospective cohort of RA patients in remission or with low disease activity was divided into a vaccination group and a non-vaccination group based on their COVID-19 vaccination status. Each of them was examined ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…RA is a systemic disease characterized primarily by autoimmune dysregulation. Although our prior investigations have indicated that the administration of COVID‐19 vaccines did not appear to trigger the disease flare in stable RA patients, 7,8 the effects of vaccine on the complicated immune system are still uncertain, and there are continuous reports of vaccine‐induced new‐onset or flare of RA. scRNA‐seq technique is powerful to allow researchers to study an individual cell and its gene expression patterns, which can provide a comprehensive picture of the immune response to the vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RA is a systemic disease characterized primarily by autoimmune dysregulation. Although our prior investigations have indicated that the administration of COVID‐19 vaccines did not appear to trigger the disease flare in stable RA patients, 7,8 the effects of vaccine on the complicated immune system are still uncertain, and there are continuous reports of vaccine‐induced new‐onset or flare of RA. scRNA‐seq technique is powerful to allow researchers to study an individual cell and its gene expression patterns, which can provide a comprehensive picture of the immune response to the vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…6 A couple of previous studies found that RA flare requiring treatment adjustment following COVID-19 vaccination was uncommon. 7,8 Nevertheless, it has been recognized that vaccines themselves as well as adjuvants may potentially provoke autoimmunity by molecular mimicry, and subsequently trigger flare of pre-existing autoimmune diseases. 9 In theory, booster shots may lead to a more pronounced immune response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation